2021
DOI: 10.3389/fonc.2021.632189
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin, a Potential Safeguard Against Carcinoma: Role in the Tumor Microenvironment

Abstract: Tristetraprolin (TTP), a well-known RNA-binding protein, primarily affects the expression of inflammation-related proteins by binding to the targeted AU-rich element in the 3’ untranslated region after transcription and subsequently mediates messenger RNA decay. Recent studies have focused on the role of TTP in tumors and their related microenvironments, most of which have referred to TTP as a potential tumor suppressor involved in regulating cell proliferation, apoptosis, and metastasis of various cancers, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 107 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…TTP has previously been described as a 'prospective' cancer tumor suppressor (18,29,30).Here, we establish the role of TTP as a tumor suppressor in PCa and determine NF-κB activation contributes to the deleterious effects of TTP loss within tumor cells. Given the finding that TTP loss occurs early in PCa development, we used genetically engineered mouse models (GEMMs) to investigate the impact of TTP loss in combination with PTEN loss on prostate epithelial cell transformation to cancer.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…TTP has previously been described as a 'prospective' cancer tumor suppressor (18,29,30).Here, we establish the role of TTP as a tumor suppressor in PCa and determine NF-κB activation contributes to the deleterious effects of TTP loss within tumor cells. Given the finding that TTP loss occurs early in PCa development, we used genetically engineered mouse models (GEMMs) to investigate the impact of TTP loss in combination with PTEN loss on prostate epithelial cell transformation to cancer.…”
Section: Introductionmentioning
confidence: 69%
“…TTP has previously been described as a ‘prospective’ cancer tumor suppressor (18, 29, 30). Here, we establish the role of TTP as a tumor suppressor in PCa and determine NF-κB activation contributes to the deleterious effects of TTP loss within tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…ZFP36 (ZFP36 ring finger protein) is a well-known mRNA binding protein. In the tumor microenvironment, ZFP36 might reduce the growth and invasion of glioma cells by targeting IL-13 mRNA to inhibit the role of PI3K/Akt/mTOR pathways [ 73 - 75 ] . CP (ceruloplasmin) serves as a prognostic biomarker in many cancers, including bile duct cancer, bladder cancer, breast cancer, etc .…”
Section: Discussionmentioning
confidence: 99%
“…Because of its ability to bind and target ARE-containing mRNAs for rapid degradation, numerous studies have shown that TTP exhibits as tumor-suppressor. Thus, loss of TTP expression or function is closely associated with tumor progression or poor outcome in malignant tumors ( 13 , 14 ). It was known that some tumor-associated genes with ARE sequences can be subject to TTP-mediated mRNA degradation.…”
Section: Introductionmentioning
confidence: 99%